(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2022)
Pre-sowing seed treatments are crucial for improving the germination capacity of several tree species. This study aims to investigate the effect of cold stratification on the germination of five non-native pine species of the Libyan flora (P.leiophylla, P.lawsonii, P.ayacahuite, P.oocarpa, and P.radiata). These pine species have potential to be introduced into the climatic ecosystem of Al-Jabal Al-Akhdar region. Three treatments of no stratification (control), 15 days of cold stratification, and 30 days of cold stratification were applied to the selected pine species. The results revealed a significant positive effect of cold stratification on seed germination. Germination percentage increased from 46.7% when sowing without stratification (control treatment) to 70% when seeds were stratified for 15 and 30 days prior to sowing, respectively. No seed germinated during the first week in the first and second treatments while the germination percentage reached in the third treatment of 30 days of cold stratification to 24%. Germination for P.leiophylla, P.lawsonii, P.oocarpa, and P.radiata improved after applying different stratification treatments on both rate and time of germination while P.ayacahuite germination did not differ significantly with stratification compared to control treatment.